Diagnostic performance of a doppler radar-based sleep apnoea testing device - Jonathan Röcken; Andrei M. Darie; Leticia Grize; Claire Ellen Dexter; Matthias J. Herrmann; Kathleen Jahn; Werner Strobel; Michael Tamm; Daiana Stolz (BMC Pulmonary Medicine)
Abstract Background Inpatient polysomnography (PSG) is the gold standard for the diagnosis of obstructive sleep apnoea (OSA), however, both complexity and costs limit the availability of this examination. Home sleep apnoea testing devices are a diagnostic alternative in patients with increased risk of OSA. We evaluated the diagnostic performance of a Doppler radar technology based, contactless sleep apnoea testing device (CSATD) in a cohort of patients with a clinically increased risk of OSA. Methods Monocentric prospective study. Sleep monitoring with the CSATD SleepizOne + without pulse oximetry (Sleepiz AG, Switzerland) was performed simultaneously with elective inpatient PSG. PSG was analysed blinded to the CSATD results and according to AASM 2012 criteria by certified sleep physicians. The CSATD data were analysed automatically and independently by a dedicated software. Results A total of 102 patients, 60.8% male, with an average age of 55 ± 15 years and body mass index of 30 ± 6 kg/m2 were included in the analysis. The sensitivity and specificity of the CSATD for a PSG apnoea-hypopnoea-index (AHI) of ≥ 5/h were 0.89 (95%CI: 0.83–0.96) and 0.88 (95%CI: 0.73-1.0). The negative and positive predictive values were 0.62 (95%CI: 0.42–0.82) and 0.97 (95%CI: 0.94-1.0). The diagnostic agreement for the diagnosis of OSA (defined as PSG AHI ≥ 5/h) was 89.8% and 100% using a CSATD AHI threshold of ≥ 5/h (n = 79/88) and ≥ 15/h (n = 61/61). However, the concordance was poor in the classification of OSA severity, with 50% (13/26) concordance for mild, 38% (10/26) for moderate, and 76% (25/33) for severe OSA respectively. Conclusion CSATD accurately identifies patients with OSA, particularly using an AHI threshold of ≥ 15/h. However, it performs subpar in disease severity stratification. Clinical trial registration This trial was registered on the International Clinical Trials Registry Platform, ISRCTN45778591.